The Marriage Customs of the Ogan Tribe as a Representation of a Living Islamic Civilisation: An Integrative Analysis of Local Culture and Islamic Sharia - Maswari Maswari; Fitriah Fitriah; Maulani Maulani; Rumila Sari; Mohammad Syawaludin (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2026)
This study examines how the marriage customs of the Ogan ethnic group represent a form of living Islamic civilization through the integration of local culture and Islamic law. The main question addressed is how traditional practices are able to internalize and reflect Islamic values within a socio-cultural framework. Positioned within the discourse of Islamic cultural studies, this research employs a qualitative literature review method by analyzing classical and contemporary sources related to adat (customary law), Islamic jurisprudence, and local wisdom. The study utilizes an integrative theoretical approach that combines the concept of living Islam with socio-anthropological perspectives on culture. The findings reveal that Ogan marriage customs are not merely cultural rituals but constitute a dynamic process of Islamization in which values such as morality, social responsibility, and religious compliance are embedded in each ceremonial stage. Furthermore, the interaction between adat and sharia demonstrates a harmonious relationship, where local traditions function as a medium for transmitting Islamic teachings. The study concludes that Ogan customary marriage practices serve as a concrete manifestation of living Islamic civilization that sustains religious values within a localized cultural context.